Memories of Muhammad : why the Prophet matters - Safi, Omid, 1970- (New York : HarperOne, 2009)
Presents a portrait of Muhammad that reveals his centrality in the devotions of modern Muslims, exploring the role of women in Islam, tensions with other religions, and the role of cyberspace in Islam's evolution.
The world before Muhammad -- The Muhammadi revolution -- The ascension of Muhammad : face-to-face with God -- Islam as an Abrahamic tradition -- Life after the prophet, death after Hossein -- Echoes of Muhammadi grace.
Includes bibliographical references (p. [313]-330) and index.
Keywords: Muhammad, -- Prophet, -- -632 -- Biography; Islam -- Biography; Islam -- History